2023
DOI: 10.3390/educsci13030309
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Professional Development in Higher Education: The Impact of Pedagogical Training Perceived by Teachers

Abstract: This paper aims to analyze the impact of a pedagogical training program aimed to promote teacher professional development in a higher education institution in Portugal. Based on a mixed-methods approach, the study evaluates the satisfaction of 36 higher education teachers with the pedagogical training program offered and discusses its impact on teachers’ perceptions of teaching practices, conceptions, and professional development. The results from the questionnaires applied to participants, including multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Similarly, Ha et al (2021) also revealed that professional development trainings and pedagogical skills are interlinked with each other. Fernandes et al (2023) also reported that the significant effect of pedagogical trainings was self-reported by teachers. Teachers show confidence towards pedagogical trainings because such type of trainings improve their teaching practices.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, Ha et al (2021) also revealed that professional development trainings and pedagogical skills are interlinked with each other. Fernandes et al (2023) also reported that the significant effect of pedagogical trainings was self-reported by teachers. Teachers show confidence towards pedagogical trainings because such type of trainings improve their teaching practices.…”
Section: Discussionmentioning
confidence: 97%
“…Jan et al (2023) conducted a study that shows the crucial role of teachers' pedagogical knowledge, teaching practices and content knowledge in attaining learning outcomes. Fernandes et al (2023) examined the effect of pedagogical trainings on professional development of teachers. This study used mixed method research approach and collect data from higher education teachers.…”
Section: Pedagogical Content Knowledge Training and Its Effect On Tea...mentioning
confidence: 99%
“…For years, employee engagement has been examined, and Peter Ducker’s principle states that people who enjoy their jobs perform well. A school, college or university’s faculty includes instructors, lecturers, researchers, scholars and professors of various academic positions such as associate professors and assistant professors (Fernandes et al, 2023). Faculty engagement is crucial to higher education institutes’ growth and success, but the concept is new to India and little research is done on it (Raina & Khatri, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Without proper mentoring, they might feel lost navigating these new demands. Therefore, vocational colleges must provide structured onboarding and support networks for new hires [1,2] .…”
Section: Introductionmentioning
confidence: 99%